DEMONSTRASI PENGENALAN VARIASI MENU DIET DIABETES MELLITUS BAGI PENDERITA DIABETES MELLITUS TIPE 2 - Ismawanti, Zuhria; Nurzihan, Nastitie Cinintya; Prastiwi, Nining (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Diabetes mellitus (DM) is a disease that can be caused by an unhealthy lifestyle. DM treatment has four pillars in its management, namely education, DM diet management, physical activity and drug management. The recommended DM dietary arrangement is almost the same as the recommended diet in general, namely balanced nutrition in accordance with calorie needs, however DM sufferers will emphasize eating regularity in terms of eating schedules, types of food and amount of food. Based on these problems, it is necessary to demonstrate the introduction of variations in the diabetes mellitus diet menu for type 2 diabetes mellitus sufferers.This activity is carried out to increase knowledge about the variety of diabetes mellitus diet menus in type 2 diabetes mellitus sufferers.Pre-test and post-test are carried out to determine the level of understanding of the demonstration which are given. The method used was to provide a demonstration of introduction to the variation of the diabetes mellitus diet menu for people with type 2 diabetes. As many as 25 people participated in this activity from beginning to end. Based on the results of the evaluation using the post test value, it shows that there is an increase in knowledge and skills regarding the variation of the type 2 DM diet, so as to prevent complications of type 2 DM.